EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS VIDEO PADA PESERTA DIDIK SEKOLAH DASAR NEGERI 07 WONOGIRI - Riyana, Dita (STABN RADEN WIJAYA WONOGIRI JAWA TENGAH, 2023)
The digital era is an era where technological developments occur throughout the world. As a society living in the digital era, we must follow the flow of technological development that we are currently experiencing. Utilizing technology to solve problems in the world of education is a smart thing. One of the uses of technology in the world of education is using video media based on computer technology as a learning tool in the classroom. Based on this description, this article aims to test the effectiveness of video as a learning medium for elementary school students. Some conclusions drawn from the benefits of video include providing joy for students. Students are able to provide specific information and have the ability to present learning experiences that students cannot obtain outside of school, for example, the history of independence. These three advantages are what make videos considered effective. Increasing students' ability to understand concepts and increasing student motivation to learn has the ability to improve student learning outcomes. Apart from that, video media is also considered effective for elementary school students because it can fulfill these three benefits. The learning needs of elementary school students are at the concrete operational stage.